Pendekatan Teori Belajar dalam Proses Pembelajaran Akidah Akhlak di MAN Jeuram Kabupaten Nagan Raya - Herman, Herman (Al Mabhats : Jurnal Penelitian Sosial Agama, 2019)
This study tested the approach of moral aqidahs teacher in the learning process at MAN Jeuram, Nagan Raya. The results of the study concluded that the more role of aqidah teacher is as the facilitator to increasing the activeness and creativity the students are in constructing their own knowledge, finding meaning from what is being studied, finding new ideas, thoughts and ideas and concepts when constructing learning in their class . This study aims to determine the learning theory approach used by moral aqidah teachers in the learning process. This study uses a descriptive method with a qualitative approach. Then using data collection techniques through observation, interviews and documentation studies. Furthermore, the data analysis process includes: data reduction, data presentation, and data verification or conclusion drawing.